Answer:
(-2, -4)
Explanation:
Since both equations are equal to y, you can set them equal to each other:
![(3)/(2)x-1=(1)/(2)x-3](https://img.qammunity.org/2022/formulas/mathematics/high-school/5ozsraq1j2vf79o2w9z9tbagisvonzgql1.png)
Next, solve for x:
![(3)/(2)x-1=(1)/(2)x-3\\x-1=-3\\x=-2](https://img.qammunity.org/2022/formulas/mathematics/high-school/u57lh857ylva6bxm1zomb7idmii12eb1gf.png)
Finally, substitute the solution for x in one of the equations (or both) to find y:
![y=(3)/(2)(-2)-1\\y=-3-1\\y=-4](https://img.qammunity.org/2022/formulas/mathematics/high-school/v54epxd9kukpbnrweb0v5yurvielzp3ccy.png)
![y=(1)/(2)(-2)-3\\y=-1-3\\y=-4](https://img.qammunity.org/2022/formulas/mathematics/high-school/c3thmwix9tb8wwtpxo5d627gs9s05jc5ne.png)
Therefore, the solution to the system of equations is (-2, -4).